Polypropylene Composites Reinforced with Lignocellulose Nanocrystals of Corncob: Thermal and Mechanical Properties - Santos-Ventura, Edgar Mauricio (2024)
Composites based on recycled polypropylene (PP) reinforced with cellulose nanocrystals whit lignin corncob were prepared. The effect of the ratio composites prepared via a compression molding process on the mechanical and thermal properties was analyzed. Corncobs is a little-used agroindustrial residue with a high cellulose content. The corncob was milled and then delignified via the organosolve process in order to get the cellulose unbleached. An acid hydrolysis process was then carried out to obtain lignocellulose nanocrystals (LCNCs). Subsequently, LCNC/PP composites were obtained via termocompression molding using different concentrations of LCNC (0, 0.5, 1 and 2% by weight) previously mixed via extrusion. The residual lignin present in the LCNCs improved the compatibility between the reinforcement and the PP matrix. This was evidenced by the increase in mechanical properties and the stabilization of thermal properties. The results of the mechanical tests showed that the LCNC increases the tensile and flexural modules and strength with respect to neat PP. Composites with 2% of LCNC showed an increase of 36% and 43% in modulus and tensile strength, respectively, while the flexural modulus and strength increased by 7.6%. By using reinforcements of natural and residual origin (corncob) and improving the properties of recycled polymers, their reuse will increase, and this can lead to reducing waste in the environment.